Elements and elasmobranchs: hypotheses, assumptions and limitations of elemental analysis. Issue 2 (13th November 2016) - McMillan, M. N.; Izzo, C.; Wade, B.; Gillanders, B. M.
Abstract : Quantifying the elemental composition of elasmobranch calcified cartilage (hard parts) has the potential to answer a range of ecological and biological questions, at both the individual and population level. Few studies, however, have employed elemental analyses of elasmobranch hard parts. This paper provides an overview of the range of applications of elemental analysis in elasmobranchs, discussing the assumptions and potential limitations in cartilaginous fishes. It also reviews the available information on biotic and abiotic factors influencing patterns of elemental incorporation into hard parts of elasmobranchs and provides some comparative elemental assays and mapping in an attempt to fill knowledge gaps. Directions for future experimental research are highlighted to better understand fundamental elemental dynamics in elasmobranch hard parts.